2012
DOI: 10.1017/s0269888912000173
|View full text |Cite
|
Sign up to set email alerts
|

Zero intelligence in economics and finance

Abstract: This paper reviews the Zero Intelligence (ZI) methodology for investigating markets. This approach models individual traders, operating within a market mechanism, who behave without strategy, in order to determine the impact of the market mechanism and consequently the effect of trader behaviour. The paper considers the major contributions and models within this area from both the economics and finance communities before examining the strengths and weaknesses of this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…LiCalzi and Pellizzari (2008) have shown that the allocative efficiency of the CDA would drop substantially if every transaction did not force agents to submit new orders. Nevertheless, as pointed out in the recent reviews by Duffy (2006) and Ladley (2012), the ZI methodology is useful in studying market design questions, because any effect of design on efficiency under ZI behavior should be attributed solely to the change of market rules.…”
Section: Introductionmentioning
confidence: 99%
“…LiCalzi and Pellizzari (2008) have shown that the allocative efficiency of the CDA would drop substantially if every transaction did not force agents to submit new orders. Nevertheless, as pointed out in the recent reviews by Duffy (2006) and Ladley (2012), the ZI methodology is useful in studying market design questions, because any effect of design on efficiency under ZI behavior should be attributed solely to the change of market rules.…”
Section: Introductionmentioning
confidence: 99%
“…The goal there is to differentiate effects due to the market mechanism, and effects due to trader strategy: if a phenomenon shows up even when the agents enter into transactions at random, then the phenomenon is due to market effects only Ladley [2013]. In both economics and in econophysics, the behaviour of zero intelligence agents is not taken to represent that of real economic actors.…”
Section: Against Burglar Economicsmentioning
confidence: 99%
“…The order-restriction rule is de¯ned as an additional parameter, 2 ½0:0; 1:0, which corresponds to the number of buyers who are probabilistically selected. In the conventional CDA model, an asynchronous update rule can be de¯ned as the one that randomly selects an agent who bids or asks at a given moment [37]. If the selected agent can bid higher than the limit price set by the seller, the buyer and seller can enter into a contract.…”
Section: Asynchronous Trading Represented By Order Restrictionmentioning
confidence: 99%